Assessment on the distribution of Araceae at different altitudes and forest types in Kelantan, Peninsular Malaysia - Logaraj, Ramakreshnan (2015)
Araceae belongs to the family of robustly monophyletic, monocotyledonous and tropical plants which are found in various habitats ranging from swamps, ponds, lakes, rivers, forests and even in paddy fields. There is a question regarding the influence of altitude on Araceae distribution since the habitat attributes often vary with altitude variations. Moreover, altitudes are mainly referred to categorize forests in Malaysia. On the other hand, the distribution of Araceae in Kelantan is still not fully explored although certain studies revealed that only 42 species from 15 genera are collected from more than one locations. Hence, this study is developed with the aim to establish a comprehensive list of Araceae found in the state, assess the relationship of altitude and forest types on species distribution as well as to testify the significance of that relationship. Data from both field work and literature review from sixty one study areas was used to prepare a list of Araceae in Kelantan. Besides, GIS applications are used to produce distribution maps of each species of Araceae at different altitudes and forest types. The strength of association between these two variables is computated using correlation analysis in SPSS. The results indicate that there are 71 species belonging to 18 genera recorded with Homalomena representing the richest genus in Kelantan. In addition, Rhaphidophora records the second dominance of species diversity whereas both Anadendrum and Scindapsus represent the third highest species diversity in Kelantan. On the other hand, genera such as Amydrium, Apoballis, Furtadoa, Lasia, Pipthospatha and Typhonium record the least species diversity in the state. Moreover, genera such as Aglaonema, Alocasia, Anadendrum, Amorphophallus Amydrium, Colocasia, Homalomena, Lasia, Rhaphidophora, Schismatoglottis and Scindapsus showed a significant association towards altitude variations. Furthermore, Lowland Dipterocarp forest consists the most number of species compared to Hill and Upper Hill Dipterocarp forests. Limestone forest is also very promising to many genera such as Amorphophallus, Homalomena, Schismatoglottis and Rhaphidophora. Therefore, reforestration, buffer zone declarations and amendments of more stern rules and regulations could be some of the strategies which can help the species to survive continuously in forested areas